Metaphors of Happiness in English and Russian - Csillag Andrea (Romanian Journal of English Studies, 2016)
According to Ekman et al. (1972), happiness is one of the six universal basic human emotions. Kövecses (2000) claims that certain aspects of the conceptualization of emotions are universal or nearuniversal. The paper compares linguistic expressions to discuss the question of the universality of the emotion happiness and its metaphors in English and Russian.